The Phenomenon of Deviation (Ecart) in Ba’iyyat Antara bin Shaddad - Ali Ghanim Falhi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
There is no doubt that pre-Islamic poetry which is an integrated fabric, with its semantic contents, expressive and creative abilities, is not different from modern poetic texts in terms of efficiency and ability.This study has dealt with the phenomenon of deviation (ecart) as one of the topics that modern stylistic studies have worked on, and unveiled the types of deviation; pictorial, synthetic and rhythmic in Ba’iyyat Antara bin Shaddad, which were unique to this poem rather than other poetic texts.DOI /10.54633/2333-021-042-030